Research status and prospect of clean and high-value utilization of HyperCoal in China - Ya-jie WANG; Hai-bin ZUO; Jing-xiu WANG; Kai-kai BAI; Jian-sheng CHEN; Tao RONG (工程科学学报, 2021)
China is the world’s largest coal-producing country; coal is very important to Chinese energy structure. However, the excess use of coal has caused serious environmental pollution and the greenhouse effect. Therefore, an indispensable way to solve this coal utilization problem is the development of clean coal technology, which is also essential for the sustainable development of China’s economy. HyperCoal (HPC), a coal derivative obtained by solvent extraction with the properties of low ash content, low moisture, high calorific value, high reactivity, good thermoplasticity, and environmental friendliness, has excellent application in clean coal technology. In terms of combustion, HPC can be used as an advanced fuel for fuel cell and chemical cycle combustion for improving combustion efficiency. Regarding gasification and liquefaction, HPC can be used in the integrated coal gasification combined cycle technology to reduce catalyst loss and equipment damage. In terms of coking coal blending, HPC can be used as an additive in the coking process and a binder for hot-pressed coal briquettes, which can increase the strength of coke and replace scarce coking coal resources such as fat and main coking coals. In the preparation of high-grade carbon materials, HPC can be used to prepare the pitch-based carbon fiber, activated carbon, and graphite electrodes, which considerably improves the performance of carbon materials. Therefore, HPC is valuable in the clean and high-value utilization of coal. On this basis, this paper pointed out the current research status of HPC application in China and elaborated the breakthrough with considerable research results of our team concerning coking coal blending and the preparation of crystalline graphite. However, currently, there are still some problems in the spread and the application of HPC. In the future, large-scale production issues need to be urgently solved, and in-depth research on the extraction mechanism and the action mechanism of HPC should be conducted.